Three strikes : miners, musicians, salesgirls, and the fighting spirit of labor's last century - Zinn, Howard, 1922-2010 (Beacon Press, 2002)
"Howard Zinn recounts the dramatic tale of the great coal mine strike in Colorado that culminated in the Ludlow Massacre. The story pits immigrant workers against the National Guard, Mother Jones against the Rockefellers, and corporate power against union organizing, a story that is all too familiar today." "With Dana Frank we join a sit-in strike in a Detroit Woolworth's during the Great Depression where young women slept on the floor, played games and sang songs together, and enjoyed the attention of an amused and curious public that vilified the "chain-store threat" long before Wal-Mart." "Robin D.G. Kelley's tale of a movie theater musician strike in New York gets at the heart of what defines a worker. Facing the inevitable dominance of sound movies, the musicians failed even to agree on demands, and could not prevent members of other unions from crossing their picket lines. What happens when jobs are lost to new technologies, and how can labor help?"--Jacket